Cytoprotective and antioxidant effects of free and nanostructured quercetin in tert-butyl hydroperoxide-induced cell damage - Potapovich, Alla I.; Kostyuk, Tatyana V.; Shutava, Tatsiana G.; Ramanouskaya, Tatsiana V.; Kostyuk, Vladimir A. (Experimental Biology and Biotechnology, 2025)
The cytoprotective and antioxidant effects of quercetin introduced into the cultural medium in the form of a solution in dimethyl sulfoxide and as an aqueous suspension of quercetin-loaded gelatin nanoparticles were investigated. Oxidative stress in HaCaT keratinocytes was induced by the addition of tert-butyl hydroperoxide. Its presence was determined by a decrease in intracellular levels of reduced glutathione and SH groups of proteins. The studied preparations were introduced into the serum-free DMEM medium immediately prior to tert-butyl hydroperoxide addition. Cell damage was assessed by measuring lactate dehydrogenase release and through live and dead cell assays. Apoptotic and necrotic cells were identified via flow cytometry using the staining kit containing FITC-labelled annexin V and propidium iodide. The results demonstrate that both free and nanostructured quercetin effectively mitigate oxidative damage and cell death induced by tert-butyl hydroperoxide. These findings suggest that incorporating quercetin into gelatin nanoparticles allows the use of this substance in aqueous suspensions without compromising its antioxidant properties and cytoprotective activity.